A comparative analysis of the financial ratios of listed firms belonging to the education subsector in the Philippines for the years 2009-2011 - Tugas, Florenz C. (Animo Repository, 2012)
Most financial statement analyses focus on firms belonging to industries that either contribute significantly to economic figures or posit in a highly competitive business environment. Whatever the motivation may be, financial statement analysis should be made available to all industries for reasons of comparability and benchmarking. So much so to industries that silently propel economic development and growth, of which the education subsector is. In the Philippines, there are only three listed firms in the education subsector. These are Centro Escolar University (CEU), Far Eastern University (FEU), and iPeople, Inc. (Malayan Colleges). This research paper aims to analyze the financial statements of these three firms for three periods (2009, 2010, and 2011) using liquidity ratios, activity ratios, leverage ratios, profitability ratios, and market value ratios. For liquidity, the following ratios were used: current ratio; quick or acid-test ratio; cash flow liquidity ratio; average collection period; and days payable outstanding. For activity, the following ratios were used: accounts receivable turnover; accounts payable turnover; fixed assets turnover; and total assets turnover. For leverage, the following ratios were used: debt ratio; debt to equity ratio; and times interest earned. For profitability, the following ratios were used: operating profit margin; net profit margin; return on total assets; return on equity; and basic earning power ratio. For market value, the following ratios were used: price-earnings ratio; market-book ratio; and dividend yield. Imploring a comparative approach, this research paper also seeks to come up with benchmark figures that will be useful for other firms (not publicly-listed) belonging to the education subsector. To do this, financial statements of CEU, FEU, and Malayan for the indicated periods were obtained from the Philippine Stock Exchange (PSE) website. Necessary information derived from these financial statements were summarized and used to compute the financial ratios for the three-year period. To provide a basis for analysis, for each financial ratio, the firm adjudged as the best one (using rule of thumb and ratio trends) was given three points, the next one, two points, and the last one, one point. The total points for each ratio category were then computed to arrive at an overall basis for analysis. Results showed that in terms of liquidity, FEU ranked first, followed by Malayan, then CEU; in terms of activity, FEU ranked first, followed by CEU, then Malayan; in terms of leverage, Malayan ranked first, followed by CEU, then FEU; in terms of profitability, FEU ranked first, followed by Malayan, then CEU; and in terms of market value, CEU and FEU tied for first and then Malayan followed. Overall, FEU (44 points) ranked first, followed by Malayan (40 points), then CEU (36 points).